-29=-5f-6f

Simple and best practice solution for -29=-5f-6f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -29=-5f-6f equation:


Simplifying
-29 = -5f + -6f

Combine like terms: -5f + -6f = -11f
-29 = -11f

Solving
-29 = -11f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '11f' to each side of the equation.
-29 + 11f = -11f + 11f

Combine like terms: -11f + 11f = 0
-29 + 11f = 0

Add '29' to each side of the equation.
-29 + 29 + 11f = 0 + 29

Combine like terms: -29 + 29 = 0
0 + 11f = 0 + 29
11f = 0 + 29

Combine like terms: 0 + 29 = 29
11f = 29

Divide each side by '11'.
f = 2.636363636

Simplifying
f = 2.636363636

See similar equations:

| 0.2x+1.98+3.02=4.14 | | 5r-7-3r=16 | | 3p^2+7=22p | | 2s-6s=24 | | 15x^4+24x^3-8x=0 | | -(2/9X)-(1/4)=-(3/2)-(1/6X) | | -6(1+9x)=33 | | 2p+15q=8 | | N-25=18+24 | | N-25=18+2 | | -3x^2-36x=0 | | 13+3r(4-1r)=5r-2 | | 2x+6y=19.80 | | -6p+3q=15 | | -2/7K=6/11 | | 4.5*.3+.7x=4 | | 3q-6p=15 | | -0.2222222222222222X-0.25=1.5-0.1666666666666667X | | 5b+3-7=17 | | -5x^3y/-15xy^3 | | 4x-7+5y-14=180 | | e=3t*3t*3t+2q*2q+t | | 3*(3x+4)=5*12-4*(2x-5) | | 10-5p=15p+(-6) | | 5/u-4=3 | | X-30=21 | | y+3x=25 | | 2-3(x+4)2=8 | | 9x+8x=60+20-12 | | 90+5x+3x+10=180 | | 2-3(x-4)2=8 | | 3-9cos(x)=x |

Equations solver categories